ANALYSIS OF WORKERS' COMPLIANCE WITH THE USE OF PERSONAL PROTECTIVE EQUIPMENT AT PT SAKO INDAH GEMILANG PALEMBANG - Yulfia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
The number of work accidents in Indonesia has increased from 2020 - 2022. This is in line with the discovery of 3 cases of light category work accidents at PT. Sako Indah Gemilang (SIG) from 2019-2022. This study aims to determine the relationship between knowledge, attitudes, length of service, and availability of Personal Protective Equipment with worker compliance with the use of Personal Protective Equipment for workers in the finger joint and molding production section at PT. Sako Indah Gemilang Palembang in 2023. The results of this research show that there is a relationship between knowledge and compliance with the use of Personal Protective Equipment with a P value = 0.001 and there is a relationship between attitude and compliance with the use of Personal Protective Equipment with a P value = 0.003. It is recommended that workers comply with work safety regulations regarding the use of Personal Protective Equipment when working and consistently and correctly use Personal Protective Equipment, and companies also consistently hold safety talks regarding the use of Personal Protective Equipment for workers.Keywords: Knowledge, Attitude, Years of Service, Availability, Compliance, PPE